Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4184/asj.2016.10.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Neurological Recovery of Transforaminal Debridement and Interbody Fusion versus Transpedicular Decompression in Combination with Pedicle Screw Instrumentation for Treating Thoracic and Lumbar Spinal Tuberculosis

Abstract: Study DesignRetrospective study.PurposeTo compare the neurological outcome of transforaminal debridement and interbody fusion with transpedicular decompression for treatment of thoracic and lumbar spinal tuberculosis.Overview of LiteratureFew articles have addressed the impact of neurological recovery in patients with tuberculosis who were treated by two different operative methods via the posterior-only approach.MethodsClinical and radiographic results of one-stage posterior instrumented spinal fusion for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(51 reference statements)
0
2
2
1
Order By: Relevance
“…Among the laboratory investigations, elevated ESR and CRP levels were recommended over leukocytosis, which has proven to be less useful. 20,21 While Tan et al 22 reported that ESR was a predictive factor for neurological deficits, ESR was not a predictive factor for neurological deficits in our study. Instead, our findings were consistent with those reported by Sudprasert et al, 21,23 who observed elevated CRP levels in patients with spinal TB with neurological deficits and used an earlier decline in the CRP level postoperatively to determine neurological recovery.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Among the laboratory investigations, elevated ESR and CRP levels were recommended over leukocytosis, which has proven to be less useful. 20,21 While Tan et al 22 reported that ESR was a predictive factor for neurological deficits, ESR was not a predictive factor for neurological deficits in our study. Instead, our findings were consistent with those reported by Sudprasert et al, 21,23 who observed elevated CRP levels in patients with spinal TB with neurological deficits and used an earlier decline in the CRP level postoperatively to determine neurological recovery.…”
Section: Discussioncontrasting
confidence: 70%
“…20,21 While Tan et al 22 reported that ESR was a predictive factor for neurological deficits, ESR was not a predictive factor for neurological deficits in our study. Instead, our findings were consistent with those reported by Sudprasert et al, 21,23 who observed elevated CRP levels in patients with spinal TB with neurological deficits and used an earlier decline in the CRP level postoperatively to determine neurological recovery. Similar to that study, a high CRP level (>20 mg/L) was the only laboratory indicator of neurological deficits in the univariate analysis in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…This finding can be explained by the mobility of the lumbosacral segment without the anterior column support and inadequate sacral fixation, usually inserting S1 pedicle screws only. In these cases, an interbody fusion may be added to support the anterior spinal column for spinal tuberculosis involving the lumbosacral segment [21,22] or extended sacral fixation such as S2AI screw [23] may be performed to prevent progressive kyphotic deformity. This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spinal nerve root or compressed dural sac can be secondarily restored by increasing the disc height. Although these procedures have satisfactory clinical outcomes, peri- and postoperative complications remain challenging problems [ 5 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%